The Impact of Quality Aspects of Hospital Services Towards Hospitalized Patients’ Interest In Treatment at Regional Public Hospital Prof. Dr. Aloei Saboe, Gorontalo City - Endi Rahman (Journal of International Conference Proceedings (JICP), 2018)
Satisfaction is crucial in hospital service, especially for patients. There are numerous approaches by a hospital to provide satisfactory services; this also includes marketing activities in improving the service quality. One of the approaches is to advance some factors, i.e. Reliability, Responsiveness, Assurance, Empathy dan Tangible. These factors associate with the patients’ satisfactory in asking for hospital treatment in Regional Public Hospital Prof. Dr. Aloei Saboe, Gorontalo City. The result of hypothesis testing signifies that those factors contribute to the hospitalized patients’ interest in the research site significantly. Keywords: Service Quality, Service, Satisfaction